PS-095 Analysis of materiovigilance bottom up alerts related to medical perfusion devices. (25th February 2017) - Rehn, C; Bousquet, C; Derain, L
Abstract : Background: Materiovigilance (MV) bottom up alerts related to medical perfusion devices represent 14% of all received alerts. They include several types of medical devices (MD) and may instigate incidents or risks of serious incidents Purpose: The purpose of this investigation was to conduct a risk mapping of infusion based on MV bottom up alerts to prioritise our preventive actions. Material and methods: A retrospective study of MV bottom up alerts in our establishment was conducted from October 2015 to September 2016. We applied a failure modes and effects analysis method for each bottom up alert. We quoted frequency and severity to determine net criticality and classified them as minor, major or critical. Results: A total of 80 incidents or risk of incidents was reported in our MV service. 26.25% of our MV bottom up alerts involved perfusion sets, 40% involved extensions and 33.75% a catheter. 12.5% of our MV bottom up alert were classified as minor, 53.75% as major and 33.75% as critical. Among the critical alerts (n=27), 17 cases were associated with an extension tube, 7 cases were associated with a central catheter and 3 with the perfusion line. The main risks identified were gas embolism and infectious risk. In 8 cases the cause of the incidence was the device itself. In the other cases, either the cause was not identified or it was due to misuse of the device. Conclusion: MV deals with a default of a device. Bottom up alerts received most often were related to misuse of the device. Training concentrated on prevention of gas embolism and infectious risk in infusions will be set up in partnership with our hygiene service and the nursing directorate of our institution. No conflict of interest